PENGEMBANGAN MODEL LATIHAN VARIASI PASSING BAWAH BOLA VOLLY BERBASIS SMALL-SIDED GAMES PADA EKSTRAKURIKULER VOLLY SMPN 1 BANDAR SRIBHAWONO - Sulistianta, Heru; Sidiq, Akbar Aminullah; Rifaldo, Muhammad Fajril; Siswoyo, Joan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a lower passing training variation model based on small-sided games for the volleyball extracurricular program at SMP Negeri 1 Bandar Sribhawono and to examine its feasibility and effectiveness. The study employed a Research and Development (R&D) method. The research stages included needs analysis, training model design, expert validation, product trials, and evaluation. Product validation was conducted by content experts, media experts, language experts, and learning experts. The validation results showed an average score of 93.71%, categorized as very valid, indicating that the training model was feasible for implementation. Product trials were carried out through small-scale and large-scale trials using a pre-test and post-test design involving students participating in the volleyball extracurricular program. The trial results indicated an improvement in students’ lower passing skills after the implementation of the small-sided games-based training model. Data analysis using the paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test results. Therefore, it can be concluded that the developed training model is very valid and effective in improving students’ volleyball lower passing skills.